Synchronization of Bitcoin Regulations in the Indonesian Legal System - Ayu Septyani Bellandina Sinlae; AAA. Ngurah Tini Rusmini Gorda; Kadek Januarsa Adi Sudharma (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the legal status of Bitcoin in Indonesia from the perspective of regulatory synchronization between regulatory institutions, namely Bank Indonesia, the Financial Services Authority (OJK), the Commodity Futures Trading Regulatory Agency (Bappebti), and the Ministry of Trade. The study highlights Bitcoin's striking dual status: while Bank Indonesia expressly prohibits its use as a means of payment under Law No. 7 of 2011 concerning Currency to maintain the sovereignty of the Rupiah, the government, through Bappebti, recognizes Bitcoin as a digital commodity that can be legally traded on futures exchanges. This regulatory asymmetry among these institutions not only leads to overlapping authority but also creates significant legal uncertainty for digital asset market players, weakens consumer protection efforts, and opens up loopholes for potential abuses such as money laundering and terrorism financing. This study uses a normative legal method with a statutory approach to analyze the hierarchy of norms, a conceptual approach to clarify ambiguous terminology, and a comparative legal approach to map the best regulatory models from developed jurisdictions such as Japan and Singapore. The results show that Bitcoin regulation in Indonesia has not been harmonious due to the lack of binding cross-institutional legal norms. Despite significant changes with the transfer of digital asset oversight to the Financial Services Authority (OJK) in January 2025, regulatory synchronization remains a challenge. The creation of a National Digital Asset Law as a lex specialis to integrate monetary, trade, and financial oversight functions, as well as the establishment of a coordinating body such as the National Crypto Regulatory Board (NCRB), is needed to create a unified digital asset legal system that adapts to technological developments.